Passing across the blood-brain barrier in glioblastoma multiforme (GBM) - Agata Rocka; Dominika Psiuk; Emilia Nowak; Dominika Madras; Klaudia Szumna (Kazimierz Wielki University, 2020)
Introduction and purpose: Blood-brain barrier (BBB) consists of  capillary endothelium, in which there are three types of intercellular junctions - adherent, tight and gap junctions.Efficient therapy involves delivering a therapeutic dose of drug into a specific site in the body, and maintaining this dose for adequate time afterwards. The aim of this study is to review current knowledge of new strategies in drug delivery to CNS and the effectiveness of these methods in glioblastoma multiforme (GBM) treatment. This review was performed using the PubMed database.  A brief description of the state of knowledge:  Methods for delivering drugs to the brain are divided into invasive and non-invasive. Invasive methods involve temporary disrupting tight intercellular junctions of the vascular endothelial cells and delivering drugs intracerebrally or intraventricularly during neurosurgical procedures. In recent years, there has been a growing interest in the use of nanoparticles as drug carriers to the central nervous system via blood-brain barrier. The usage of nanoparticles implies many advantages, such as non-invasive, low cost, good biodegradability, stability, ability to carry various types of agents, selectivity and ability to control drug release.  Conclusions: Limited options in treating brain located tumors, including glioblastoma multiforme, due to difficulties in drug penetration through the BBB engages scientists to search for new treatments. Crossing the BBB using invasive methods based on interruption of cell junctions show promising results, but they are associated with i.a. a high risk of uncontrolled influx of toxins to the CNS or  ion-electrolyte imbalance, which may lead to neuronal dysfunction. Invasive methods can be effective only in tumors, while treatment of diseases such as Alzheimer's disease is impossible. Recent studies show that nanoparticles would be a great, non-invasive alternative, but they are difficult to use with relatively low permeability through undamaged BBB. In some studies using nanoparticles as nanocarriers  (EDVDox) or SYMPHONY method (combining photothermal therapy with GNS and immunotherapy of checkpoints in a mouse model) against GBM shows positive results. More research is required to confirm the effectiveness and safety of these treatments.